Pengembangan Media Video Animasi Berbasis Canva dengan Model Addie pada Pembelajaran IPA untuk Meningkatkan Prestasi Belajar Siswa Kelas V di SD Negeri 2 Yehembang Kauh - Yanti, Ni Kadek Ayu Novita; Dewi, Made Sri Astika; Februyan, Irwan (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Development of Canva-Based Animation Video Media Using the ADDIE Model in Science Learning to Improve the Learning Achievement of Class V Students at SD Negeri 2 Yehembang Kauh. The aim of this research is to determine media design, media validation, media practicality, and the effectiveness of Canva-based animated video media on the Let's Get to Know Our Earth material. This research uses Research and Development (R&D) research and the model used is the ADDIE Development model. The ADDIE Development Model has several stages, namely analysis. This product was validated by 1 media expert, 1 material expert, 1 class teacher and 13 grade 5 students. In the initial stage, validation tests were carried out by media experts, material experts and teachers. Then test the effectiveness of the media in the form of pretest-posttest and validation tests by students. The validation results show that media experts obtained an average of 80% which is included in the Valid and Appropriate criteria, for validation results material experts obtained the Very Valid and Appropriate category, with results of 83.3% and student response tests and teacher responses obtained respective results of 89% and 81.8% are included in the feasible and practical criteria. The test results show that the overall average increase in learning achievement results obtained by students is 20%. It can be concluded that this animated video product based on the Canva application can improve student learning achievement in the science learning process at SD Negeri 2 Yehembang Kauh.